Activity of paromomycin against Leishmania amazonensis: Direct correlation between susceptibility in vitro and the treatment outcome in vivo. (December 2020) - Coser, Elizabeth M.; Ferreira, Bianca A.; Branco, Nilson; Yamashiro-Kanashiro, Edite H.; Lindoso, José Angelo L.; Coelho, Adriano C.
Abstract: Paromomycin is an aminoglycoside antibiotic approved in 2006 for the treatment of visceral leishmaniasis caused by Leishmania donovani in Southeast Asia. Although this drug is not approved for the treatment of visceral and cutaneous leishmaniasis in Brazil, it is urgent and necessary to evaluate the potential of this drug as alternative for the treatment against species responsible for these clinical forms of the disease. In Brazil, Leishmania amazonensis is responsible for cutaneous and diffuse cutaneous leishmaniasis. The diffuse cutaneous form of the disease is difficult to treat and frequent relapses are reported, mainly when the treatment is interrupted. Here, we evaluated paromomycin susceptibility in vitro of a L. amazonensis clinical isolate from a patient with cutaneous leishmaniasis and the reference strain L. amazonensis M2269, as well as its in vivo efficacy in a murine experimental model . Although never exposed to paromomycin, a significant differential susceptibility between these two lines was found. Paromomycin was highly active in vitro against the clinical isolate in both forms of the parasite, while its activity against the reference strain was less active. In vivo studies in mice infected with each one of these lines demonstrated that paromomycin reduces lesion size and parasite burden and a direct correlation between the susceptibility in vitro and the effectiveness of this drug in vivo was found. Our findings indicate that paromomycin efficacy in vivo is dependent on intrinsic susceptibility of the parasite. Beyond that, this study contributes for the evaluation of the potential use of paromomycin in chemotherapy of cutaneous leishmaniasis in Brazil caused by L. amazonensis . Graphical abstract: Image 1